STANDARISASI EKSTRAK ETANOL DAUN BUAS-BUAS (Premna serratifolia Linn.) DAN KAYU SECANG (Caesalpinia sappan Linn.). - Tara Kamita Riduana; Isnindar Isnindar; Sri Luliana (Jurusan Farmasi Politeknik Kesehatan Makassar, Kementerian Kesehatan RI, 2021)
Standardization Of Buas Buas Leaf (Premna serrativeolia Linn.) Ethanol Extract And Secang Wood (Caesalpinia sappan Linn.).Extract standardization is a parameter used to ensure the safety and quality of extracts before being developed into pharmaceutical preparations. Meanwhile, Buas buas leaves (Premna serrativeolia Linn.) are useful for treating gastric disorders, carminatives, hemorrhoids, diuretics, fever, constipation, shortness of breath, and also as anti-inflammatory expectorants, antioxidants, antimicrobials, and anticoagulants. Furthermore,secang wood (Caesalpinia sappan Linn.) is widely known as a nutritious herbal drink. This research aims to determine extracts standardization including specific parameters (organoleptic and phytochemical screening) and non-specific (drying losses). The multilevel maceration with n-hexane and ethanol solvents extraction method was used. The results showed that the percentage of drying shrinkage in the ethanol extract of buas-buas leaves and secang wood was 18.99% ± 0.60 and 15.27% ± 1.46 respectively. Moreover, the ethanol extract of buas-buas leaves has a thick shape, blackish-brown in color, has a distinctive aromatic odor, while secang wood has a thick, brownish-red color, as well as a distinctive aromatic odor. The Buas buas leaves extract contains flavonoids, phenolics, tannins, saponins, and terpenoids, while secang wood contains only flavonoids, tannins, and terpenoids.Keywords : Extract standardization, Graded maceration, Buas buas leaves, Secang wood.Standarisasi ekstrak merupakan parameter untuk menjamin keamanan dan kualitas ekstrak sebelum dikembangkan menjadi sediaan farmasi. Daun buas-buas (Premna serratifolia Linn.) berkhasiat sebagai mengobati gangguan lambung, karminatif, diuretik, demam, sesak nafas, ekspektoran antiinflamasi, antioksidan, antimikroba, sembelit, ambeien, dan antikoagulan. Kayu secang (Caesalpinia sappan Linn.) dikenal sebagai minuman herbal yang berkhasiat. Penelitian ini bertujuan untuk mengetahui standarisasi ekstrak meliputi parameter spesifik (organoleptis dan skrining fitokimia) dan non-spesifik (susut pengeringan). Metode ekstraksi pada penelitian ini menggunakan maserasi bertingkat dengan pelarut n-heksan dan etanol. Hasil penelitian menunjukkan bahwa persentase susut pengeringan ekstrak etanol daun buas-buas sebesar 18,99% ± 0,60 dan ekstrak etanol kayu secang sebesar 15,27% ± 1,46. Ekstrak etanol daun buas-buas memiliki bentuk yang kental, berwarna coklat kehitaman, berbau aromatik khas, sedangkan ekstrak etanol kayu secang memiliki bentuk yang kental, berwarna merah kecoklatan, berbau aromatik khas. Ekstrak etanol daun buas-buas mengandung senyawa flavonoid, fenolik, tanin, saponin, terpenoid. Sementara itu, ekstrak etanol kayu secang mengandung flavonoid, tanin, dan terpenoid.Kata kunci : Standarisasi ekstrak, Maserasi bertingkat, Daun buas-buas, Kayu secang.